Association of lifestyle and behavioral factors with self-reported visual problems among schoolchildren in rural Bangladesh - Fakir M Amirul Islam; Arzan Hosen; Abdullah Al Mahmud (PLoS ONE, 2025)
Background Lifestyle, environmental, and genetic factors influence visual impairment. The current study aims to report the sociodemographic, lifestyle, and behavioral factors associated with self-reported ocular conditions among children. Materials and methods Data were collected from 13341 children aged 7–14 from 176 primary schools and 16 madrasas (Islamic educational institutes) of Narail Upazila from 30 November 2022 to 20 August 2023. Data on sociodemographic factors, including living conditions and parents’ education; lifestyle and behavioral characteristics, including vitamin A consumption, watching TV or mobile; and self-reported ocular conditions, including seeing the blackboard or distant people, were collected. Chi-square tests and logistic regression analyses reported the association between sociodemographic characteristics with lifestyle and behavioral characteristics, and self-reported ocular conditions. The statistical software SPSS was used for data analysis. Results Of the total children, 52.5% were girls. Almost 99% had taken Vitamin A, 59% watched TV or mobile screens regularly, 99 (0.7%) children reported that they had problems seeing the blackboard or distant people, only 59 (0.4%) children had eye examinations previously, and 32 (0.2%) children used spectacles even if they had experienced any adverse ocular conditions. The proportion of children watching TV (67% vs. 58%) or mobile screens (69.6% vs. 57.6%) was higher in urban than rural areas. The proportion of children who had problems seeing blackboard was higher in urban areas (2.2% vs. 0.6) than in rural areas and among mothers with higher education (3.1% among graduate mothers vs. 0.3% among mothers without schooling). More than 99% of children had no eye examination before this screening program. Watching TV one-hour relative risk 4.16, (95% confidence interval (CI): 2.15–8.07 or more than one hour RR 5.33, 95% CI: 2.62–10.8 was associated with a higher proportion of seeing problems than those who did not watch TV. Those who used mobile for one hour, 4.82, (95% confidence interval (CI): 2.17–10.7 or more than one hour RR 7.30, 95% CI: 3.06–17.4 was associated with a higher proportion of reporting any ocular trauma than who did not use mobile phone. Conclusion Vitamin A taken among schoolchildren is very high, and self-reported ocular problems are minimal. Children living in urban areas are more prone to behavioral risk factors for visual impairment and have a higher proportion of ocular trauma. Increased awareness of vision impairment and its risk factors by schoolteachers can be a feasible and cost-effective approach to improving eye health in schoolchildren, especially in resource-poor setting.